Compensation Strategies in Muhadatsah Learning: A Case Study of Speaking Anxiety, Self-Confidence, and Motivation among Beginner Arabic Learners - Erlina Erlina; Renti Yasmar; Nur Naria Dina Romadhon; Isra Hayati Darman (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2026)
This research is motivated by the improvement of the mahaarah al-kalaam ability of PBA STAIN Madina students whose previous education base was Salafiyah boarding school. This study aims to explore the implementation of compensation strategy as a direct strategy in muhadatsah learning in PBA STAIN Madina Study Program, supporting and inhibiting factors and their implications for mahaarah al-kalaam skills. Data were collected using observation and online interview techniques. Data were analyzed based on Miles and Huberman's analysis, namely data reduction, data display, and verification. The findings of this study are 1) the implementation of compensation strategies is integrated into other strategies in muhadatsah 1 learning for beginner-level students 2) there are various supporting and inhibiting factors in the implementation of compensation strategies both internally and externally, and 3) muhadatsah lecturers and students recognize the implications of implementing compensation strategies in the form of reducing shyness and anxiety, increasing self-confidence and motivation and fostering a sense of pleasure in mahaarah al-kalaam. This research has implications as a foundation and reference for Arabic language teachers and lecturers everywhere in applying compensation strategies as a solution to the limitations of oral language skills for beginners.